SEMIOTIC FEATURES OF APOLOGY IN A GERMAN BUSINESS SPEECH ACT (EXAMPLE OF EMAILS) (Scientific journal of the Fergana State University, 2024)
The article examines the semiotic aspects of the use of the word sorry in the German business speech act. The research material is based on examples of German language business e-mails collected from personal correspondence of German business companies. Apologies in business e-mails are studied from the perspective of pragmalinguistics and interpreted as social speech acts. Apology is understood as an important integral part of communication. Apology is used in German communicative practice to regulate interpersonal relationships, as well as in the process of business communication, intentionally or unintentionally, to be aware of etiquette and moral standards. As in other languages, in German there are peculiarities in the business speech act that activate the motivation to restore the company's reputation by apologizing. The speech act of "apology" in a German business e-mail is semiotically studied in three positions: pragmatic, semantic and syntactic. In German, the speech act of "apologising" is based on reciprocal speech acts that serve to defuse conflict. In our work, tactics that help to achieve a positive result of communication were considered - tactics of reconciliation, tactics of interpretation, tactics of admitting guilt.